Нейромережева система наведення і стабілізації з регулятором на основі еталонної моделі Model Reference Controller - Кузнецов, Б.І.; Василець, Т.Ю.; Варфоломієв, О.О. (Електротехніка і електромеханіка, 2015)
Виконано синтез системи наведення і стабілізації з застосуванням нейромережевого регулятора на основі еталонної
моделі Model Reference Controller. Наведена структура і принцип дії нейрорегулятора. Розроблена схема системи наведення і стабілізації з пропорційнио-диференційним регулятором у контурі положення і нейромережевим регулятором
у контурі швидкості. Проведено моделювання нейромережевої системи на ЕОМ і виконано аналіз динамічних характеристик системи. Выполнен синтез системы наведения и стабилизации с применением нейросетевого регулятора на основе эталонной
модели Model Reference Controller. Приведена структура и принцип действия нейрорегулятора. Разработана схема
системы наведения и стабилизации с пропорционально-дифференциальным регулятором в контуре положения и нейросетевым регулятором в контуре скорости. Проведено моделирование нейросетевой системы на ЭВМ и выполнен
анализ динамических характеристик системы. The aim of this work is the synthesis of neural network aiming
and stabilization system for the special equipment of moving
objects with neuro-controller on the basis of standard model
and performance comparison of the neural network system with
the neural network predictive control. Build a block diagram of
the neural network aiming and stabilization system, based on
the subject control principle with PD-regulator in the position
loop and with neuro-controller on the basis of standard model
in the in the velocity loop. The neuro-controller on the basis of
standard model Model Reference Controller is synthesized in
the MATLAB Neural Network Toolbox and system simulation is
performed. The studies show that the transient state variables of
the system are oscillatory. Therefore, the neuro-controller with
the prediction NN Predictive Controller should be used for aiming and stabilizing system to provide high dynamic characteristics achieved at the cost of higher complexity and computational
cost.